Subcutaneous IL-6 Inhibitor Sarilumab vs. Standard Care in Hospitalized Patients With Moderate-To-Severe COVID-19: An Open Label Randomized Clinical Trial - García-Vicuña, Rosario; Rodriguez-García, Sebastián C.; Abad-Santos, Francisco; Bautista Hernández, Azucena; García-Fraile, Lucio; Barrios Blandino, Ana; Gutiérrez Liarte, Angela; Alonso-Pérez, Tamara; Cardeñoso, Laura; Alfranca, Aránzazu; Mejía-Abril, Gina; Sanz Sanz, Jesús; et al. (Frontiers in Medicine, 2022)
Background: The use of IL-6 blockers in COVID-19 hospitalized patients has been associated to a reduction in mortality compared to the standard care. However, many uncertainties remain pertaining optimal intervention time, administration schedule and predictors of response. To date, data on the use of subcutaneous sarilumab is limited and no randomized trial results are available. Methods: Open label randomized controlled trial at a single center in Spain. We included adult patients admitted with microbiology documented COVID-19 infection, imaging confirmed pneumonia, fever and/or laboratory evidence of inflammatory phenotype and no need for invasive ventilation. Participants were randomly assigned to receive sarilumab, a single 400 mg dose in two 200 mg subcutaneous injections, added to standard care or standard care in a 2:1 proportion. Primary end points included 30-day mortality, mean change in clinical status at day 7 scored in a 7-category ordinal scale ranging from death (category 1) to discharge (category 7), and duration of hospitalization. The primary efficacy analysis was conducted on the intention to-treat population. Results: Thirty patients underwent randomization: 20 to sarilumab and 10 to standard care. Most patients were male (20/30, 67%) with a median (interquartile range) age of 61.5 years (56-72). At day 30, 2/20 (10%) patients died in the sarilumab arm vs none (0/10) in standard care (Log HR 15.11, SE 22.64; p 0.54). At day 7, no significant differences were observed in the median change in clinical status (2 [0-3]) vs 3 [0-3], p 0.32). Median time to discharge (days) were similar (7 [6-11] vs 6 [4-12]; HR 0.65, SE 0.26; p 0.27). No significant differences were detected in the rate of progression to invasive and noninvasive mechanical ventilation. Conclusions and relevance: Our pragmatic pylot study has failed to demonstrate a benefit of adding subcutaneous sarilumab to standard care for mortality by 30 days, functional status at day 7, or hospital stay. Findings herein do not exclude a potential effect of sarilumab in severe COVID-19 but adequately powered blinded randomized phase 3 trials are warranted to assess the impact of the subcutaneous route and a more selected target population. Trial Registration: ClinicalTrials.gov Identifier: NCT04357808